Locating the Ancient Toponym of "Kindāu": The Recognition of an Indo-European God in the Assyrian Inscriptions of the Seventh Century BC. Issue 2 (2nd July 2020) - Rezaie, Iraj
ABSTRACT: "Kindāu" is the name of an ancient fortress located in the west of Iran, which has been mentioned three times in the inscriptions of the Assyrian king, Sargon II. So far, no comment has been made by researchers about the location and terminology of this toponym. The author believes that the second part of this name, i.e. "dāu", represents the ancient god of the "sky" in the beliefs of Indo-European peoples. This new view opens a new perspective to the dark field of Median religion studies. The results of this research reveals that despite religious revolutions and the obvious opposition of Zoroastrianism against some ancient gods, the belief in the god of heaven was common in the ancient land of Medes, and amazingly, this belief has continued up to the contemporary era. The author believes that "Dāwūd" and "Tāwūs", two main angels in "Ezdī" and "Yārī" religions, are probably, the same old god of the "sky". In addition, the author believes that a feasible option for locating "Kindāu" is probably, the district of "Kal-i- Dāwūd" near the city of "Sar-i Pul-i Zahāb". Abbreviations: ARAB I: Luckenbill, D. D. Ancient Records of Assyria and Babylonia: Historical Records of Assyria from Sargon to the End, vol. I. Chicago: University of Chicago Press, 1926.; ARAB II: Luckenbill, D. D. Ancient Records of Assyria and Babylonia: Historical Records of Assyria from Sargon to the End, vol. II. Chicago: University of Chicago Press, 1927.; CAD: The Assyrian Dictionary of the University of Chicago. Chicago: The Oriental Institute, 1964.